Aristolochia chlamydophylla (Aristolochiaceae), a New Record for the Flora of Vietnam - Oanh, Pham Thi; Hung, Lai Viet; Trung, Nguyen Thanh; Truong, Do Van (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4745, 2018)
Abstract: Aristolochia chlamydophylla C.Y. Wu ex S.M. Hwang, a medicinal plant and main distribution from northern Thailand and south-eastern China, is newly recorded for the flora of Vietnam. This species was misidentified to A. kaempferi in Vietnamese herbaria. An extent description, illustrations and taxonomic notes of Aristolochia chlamydophylla are also provided.